Primary Vaginal Carcinoma, Tales of Tragedy : Case Report (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Primary carcinoma of vagina is a rare entity in gynaecological oncology. Carcinoma of vagina in prolapsed uterus is extremely rare. A tumour should be considered as a primary vaginal carcinoma when cervix is uninvolved. Here two cases of primary vaginal carcinoma are reported. These cases were confirmed by histopathology and exclusion of carcinoma cervix, endometrium and ovary through meticulous physical examination and relevant investigations. These two patients were treated by radiotherapy. Chattagram Maa-O-Shishu Hospital Medical College Journal Volume 12, Issue 3, September 2013: 64-66